2013
DOI: 10.1111/mbe.12016
|View full text |Cite
|
Sign up to set email alerts
|

A Rhythmic Musical Intervention for Poor Readers: A Comparison of Efficacy With a Letter‐Based Intervention

Abstract: There is growing evidence that children with reading difficulties show impaired auditory rhythm perception and impairments in musical beat perception tasks. Rhythmic musical interventions with poorer readers may thus improve rhythmic entrainment and consequently improve reading and phonological skills. Here we compare the effects of a musical intervention for poor readers with a software intervention of known efficacy based on rhyme training and phoneme‐grapheme learning. The research question was whether the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
149
1
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 170 publications
(166 citation statements)
references
References 26 publications
12
149
1
4
Order By: Relevance
“…Given that both music training and JROTC training enhance phonological awareness and involve synchronization with perceptual cues, future work comparing music training to a passive control group could reveal a divergence not reported here. On the other hand, we found no gains in rapid naming or phonological memory, despite the fact that both reading (46)(47)(48)(49)(50) and verbal memory (30)(31)(32)(33)(34)(35)(36)(37)(38) have been associated with music training in other studies, suggesting either that the training studied here was not optimally designed to enhance these skills or that enhancing these skills requires a greater amount of training or training begun earlier in life. A third possibility is that the link between phonological processes and beat synchronization is restricted to phonological awareness.…”
Section: Discussioncontrasting
confidence: 49%
“…Given that both music training and JROTC training enhance phonological awareness and involve synchronization with perceptual cues, future work comparing music training to a passive control group could reveal a divergence not reported here. On the other hand, we found no gains in rapid naming or phonological memory, despite the fact that both reading (46)(47)(48)(49)(50) and verbal memory (30)(31)(32)(33)(34)(35)(36)(37)(38) have been associated with music training in other studies, suggesting either that the training studied here was not optimally designed to enhance these skills or that enhancing these skills requires a greater amount of training or training begun earlier in life. A third possibility is that the link between phonological processes and beat synchronization is restricted to phonological awareness.…”
Section: Discussioncontrasting
confidence: 49%
“…The disorder has also been linked to poor rhythmic processing in both auditory and motor domains (52). An intervention study (53) demonstrated that rhythmic musical training enhanced the reading skills of poor readers by similar amounts compared with a well-established letter-based intervention. Our study hints at a mechanism for these results: providing musical and rhythmic training enhances cortical entrainment such that children with initially weak entrainment can improve, thereby alleviating one key hypothesized cause of dyslexia.…”
Section: Discussionmentioning
confidence: 99%
“…Similar intervention in conjunction was suggested for musical training aiming to improve reading abilities [190][191][192].…”
Section: Discussionmentioning
confidence: 99%